Pengaruh Pajak Hiburan, Hotel, Restoran, dan Reklame terhadap PAD Kota Batu - Harum Syabrinawati; Sjarief Hidajat (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2023)
Original Local Government Revenue is a source of financing for the Local Government, one of which is obtained from Local Taxes. Local tax revenue changes every year due to various factors. Batu City is a tourist city that has the potential for high local tax revenues because of many entertainment facilities, hotels, restaurants, and billboards. However, the emergence of the covid pandemic has led to many new policies such as tax relaxation, which also applies in Batu City. This study aims to determine the effect of Entertainment Tax, Hotel Tax, Restaurant Tax And Advertising Tax on Original Local Government Revenue in Batu City. The type of research used is quantitative research using secondary data obtained from the Central Bureau of Statistics of Batu City and Performance Accountability Reports of Government Agencies of Batu City Regional Finance Agency for 2013-2020. The sampling technique in this study is the Saturated Sampling technique by using the entire population obtained. Hypothesis are tested in this study using multiple linear regression models. The results of the study indicate that the Entertainment Tax, Hotel Tax, and Advertising Tax have an effect on and contribute to Original Local Government Revenue in Batu City. Meanwhile, the Restaurant Tax has no effect and does not contribute to Original Local Government Revenue in Batu City. Keywords: Entertainment Tax, Hotel Tax, Restaurant Tax, Advertising Tax, Original Local Government Revenue